REPEATABILITY ESTIMATION OF SEMEN PRODUCTION AND QUALITY OF LOCALS MADURA CATTLE BREED (Bos indicus) - Prihatin, Koko Wisnu; Hakim, Luqman; Maylinda, Sucik (Jurnal Kedokteran Hewan, 2017)
The objective of this study was to evaluate the effect of genetic and environmental factor on locals Madura cattle semen production and quality. A total of 2275 semen collections records from 11 bulls from 2012 to 2014 were analyzed to evaluate the genetic potency of semen productions. Genetic evaluation consists of repeatability estimation of semen volume, sperm concentration and sperm individual motility. Data were analyzed by HGLM (REML) with environmental factors of age, seasons, interval of semen collections, and frequency of ejaculations as fixed effect and bulls as random effect using GENSTAT 16th edition. Result showed that age and ejaculation frequency affect to all variables; interval of semen collections affected to both semen volume and sperm concentrations; while seasons only affected to sperm concentrations. Repeatability estimation of semen volume, sperm concentration and sperm individual motility were 0.376, 0.445 and 0.567 respectively. It was concluded that the quality of Madura bulls ejaculate less affected by environmental factors.